Problematika dalam Evaluasi Studi Pembelajaran Pendidikan Islam - Ruqoiyah Ruqoiyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
Abstract: Islamic educational institutions such as madrasas and Islamic boarding schools have succeeded in building human character with a religious culture that loves the Republic of Indonesia. The slanted view of informal institutions